2010
DOI: 10.5251/ajsir.2010.1.2.309.313
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the critical sources of investment finance in Nigeria: a factor analytical approach

Abstract: The paper aimed at investigating the most critical sources of investment finance in Nigeria. To do this, factor analysis technique and the multiple regression analysis were used as alternate methods. The two techniques were used for the ascertainment of the authenticity or validity of the results. The empirical results from both methods revealed that savings and private sector credits are the most crucial sources of investment finance in Nigeria. In the light of this finding, the researcher recommends that gov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Financial institutions must pool savings and direct them through viable investment if growth must take place. Private sector credit and retention of earnings are very significant in the finance of business concern (Okpara, 2010). Therefore a farmer need to have access to credit and retain some of its earning to enhahce growth of his farm holdings.…”
Section: Methodsmentioning
confidence: 99%
“…Financial institutions must pool savings and direct them through viable investment if growth must take place. Private sector credit and retention of earnings are very significant in the finance of business concern (Okpara, 2010). Therefore a farmer need to have access to credit and retain some of its earning to enhahce growth of his farm holdings.…”
Section: Methodsmentioning
confidence: 99%
“…Companies mainly consider liquidity positions when making dividend decisions (Alshammari, 2012;Deshmukh, Goel, & Howe, 2013;Islam & Adnan, 2019;Khan & Ahmad, 2017). Okpara and Godwin (2010) also found a significant optimistic relationship between liquidity and DPP.…”
Section: Liquiditymentioning
confidence: 98%
“…Return on Equity (ROE) is adopted by Le et al (2019) as a proxy for a firm's profitability measures. The variable Liquidity (Leq) has been taken from Okpara and Godwin (2010); Leverage (Lev) from Alzomaia (2013); Firm Size (FS) from Fama and French (2001); Dividend Payout Ratio of Previous Year (PDPR) from Fitri et al (2016); Corporate Tax Ratio (CTR) from Rehman and Takumi (2012) and Capital Adequacy Ratio (CAR) from Yesyurun (2021). The…”
Section: Research Instrumentsmentioning
confidence: 99%
“…They also concluded that more profitable firms pay larger dividends. Additionally, Okpara (2010) observed that earnings, current ratio (liquidity) and previous years dividends exerts a positive influence on the dividend pay-out ratio in Nigeria's firms.…”
Section: Introductionmentioning
confidence: 97%